ON THE EXISTENCE OF UNIQUE COMMON FIXED POINT OF TWO MAPPINGS IN A METRIC-LIKE SPACE - Mitra, Mainak; Bhutia, Jigmi Dorjee; Tiwary, Kalishankar (International Journal of Engineering Technologies and Management Research, 2022)
The main objective of this article is to introduce a fixed-point result involving two mappings satisfying contraction in a metric-like space. The article has been designed in the following manner. In the first section the authors have mentioned some definitions and commonly used notations. In the second section, they have mentioned some fixed-point results. In the third section the authors have introduced their main result and in the last section, using these results, the authors have obtained some conditions that assure the existence of a common fixed point of a pair of mappings.